Vortex Flow‐controlled Circularly Polarized Luminescence of Achiral Pt(II) Complex Aggregates Assembled at the Air‐Water Interface. Issue 12 (26th October 2022) - Maeda, Takatoshi; Mori, Taizo; Ikeshita, Masahiro; Ma, Shing Cho; Muller, Gilles; Ariga, Katsuhiko; Naota, Takeshi
Abstract: Circularly polarized luminescence (CPL) has been researched for various applications by control of characteristics such as chirality and magnitude. Supramolecular chirality has been prepared by vortex motion as a mechanical stimulus; however, CPL has yet to be controlled precisely and reproducibly. In this work, the first precise control of CPL under vortex flow conditions at an air‐water interface is reported. The supramolecular chirality of aggregates consisting of an achiral trans‐bis(salicylaldiminato)Pt(II) complex bearing hexadecyl chains is induced and controlled with vortex flow at the air‐water interface, whereas the complex naturally forms an achiral amorphous solid with non‐chiroptical properties under non‐vortex conditions. The CPL direction and magnitude ( g lum value) of the Pt(II) complex aggregates can be adjusted precisely according to the vortex conditions, including the rotatory direction and flow rate. Vortex‐flow‐induced emission enhancement is also observed upon an increase in the rate of the vortex flow. Abstract : Circularly polarized luminescence (CPL) of aggregates consisting of achiral trans‐bis(salicylaldiminato)Pt(II) complex 1a bearing hexadecyl chains can be generated and controlled precisely by aggregation at air‐water interface with vortex flow, while aggregates formed at static air‐water interface without vortex do not exhibit CPL. Direction and glum value of the CPL property can be adjusted by the vortex direction and rotation speed.